Краткий биографический словарь композиторов - Вайнкоп Юлиан Яковлевич (Просвещение, 1988)
Экземпляры: БС (20170302) / Инвентарный номер: РТШ47666 / Сис.шифр: 85.31 / Авт.знак: В 14 / ГРНТИ: 18.41 / ББК: 85.313(0)